2021
DOI: 10.1038/s41598-021-87968-4
|View full text |Cite
|
Sign up to set email alerts
|

Edelfosine nanoemulsions inhibit tumor growth of triple negative breast cancer in zebrafish xenograft model

Abstract: Triple negative breast cancer (TNBC) is known for being very aggressive, heterogeneous and highly metastatic. The standard of care treatment is still chemotherapy, with adjacent toxicity and low efficacy, highlighting the need for alternative and more effective therapeutic strategies. Edelfosine, an alkyl-lysophospholipid, has proved to be a promising therapy for several cancer types, upon delivery in lipid nanoparticles. Therefore, the objective of this work was to explore the potential of edelfosine for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 68 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Due to its benign early imaging features and rapid growth, it is found in the middle and late stages, and there is no targeted treatment due to the lack of effective targets, which has always been a difficult problem in clinical practice. [ 23 ] In recent years, with the improvement of the resolution of ultrasound instruments and the diversification of imaging modes, the exploration of breast imaging has been continuously improved.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its benign early imaging features and rapid growth, it is found in the middle and late stages, and there is no targeted treatment due to the lack of effective targets, which has always been a difficult problem in clinical practice. [ 23 ] In recent years, with the improvement of the resolution of ultrasound instruments and the diversification of imaging modes, the exploration of breast imaging has been continuously improved.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, preparation was carried out in two steps: firstly, covalent conjugation/binding between PEG and aptamer sequence was performed (attending to the reactive groups of each other and specifications described below) in a ratio of 5 : 1 (PEG : aptamer). Next, the nanoemulsion was formed following the ethanol injection method slightly modified 26,51,52 by adding the organic phase (containing stock solutions of vitamin E and Sphingomyelin at 200 and 40 mg mL −1 in ethanol, respectively) to the aqueous phase composed of the PEG-aptamer conjugate, resulting in a molar ratio of VitE : SM : PEG of 1 : 0.1 : 0.01. All nanoconjugate formulations were scaled up to a final volume of 400 µL.…”
Section: Preparation Of Surface Decorated Nanoemulsions By Covalent B...mentioning
confidence: 99%
“…Furthermore, it was observed that the ET-NEs penetrated the physiological barriers of MDA-MB 231 xenografted zebrafish embryos, resulting in a significant reduction of cancer cell proliferation, which was further confirmed by confocal laser microscopy. Further, it was observed that the ET-NEs showed a dose-dependent IC 50 which was found to be 6.9 μg/mL at 13.2 μM after 24 h of incubation, whereas the free ET showed a higher IC 50 which is 13.9 μg/mL at 26.5 μM [ 65 ].…”
Section: Lipid-based Nanoparticles: a Versatile Drug Delivery Systemmentioning
confidence: 99%